THE RE-ADAPTATION OF THE ENVIRONMENTAL ZONING OF THE IRATI FLONA FROM THE RELIEF REPRESENTATION INDEXES - Maganhotto, Ronaldo Ferreira; Lohmann, Marciel; Souza, Luiz Claudio de Paula (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.864, 2019)
Brazilian protected areas list a number of difficulties, including irregularities in management plans and environmental zoning. Thus, it was proposed and justified, through the Relief Representation Indexes, the readjustment of the Environmental Zoning of Irati’s Flona. For this, after the selection and processing of the IRRs, using the Fuzzy Logic and Multiple Criteria Analysis, the spatialization of the Flona Limiting Classes was obtained. The result showed changes in the limits of the Management and Recovery Zones, as well as the incorporation of the Intangible Zone. Thus, the procedures allowed the compatibility between areas of greater fragility to more restrictive zones and places of less susceptibility to erosion and sedimentation processes to more permissive zones.